Prognostic Significance of DNA Cytometry in Carcinoma of the Uterine Cervix FIGO Stage IB and II - Hans Jürgen Grote; Nicolaus Friedrichs; Natalia Pomjanski; Helen Friderike Guhde; Olaf Reich; Alfred Böcking (Analytical Cellular Pathology)
Objective: To assess the prognostic value of DNA‐image cytometry in cervical carcinoma of the uterus and its relation to other established prognostic factors. Study design: The study included 116 cases of cervical carcinoma FIGO stages IB and II which were treated with radical abdominal hysterectomy. The median follow‐up was 55 months (range 1–162 months). DNA image cytometry was performed on cytologic specimens prepared by enzymatic cell separation from formalin‐fixed, paraffin‐embedded tissues. DNA stemline ploidy, DNA stemline aneuploidy, 5c exceeding rate, 9c exceeding rate, 2c deviation index, and DNA malignancy grade were computed. DNA‐variables as well as various clinical and histological variables were related to survival rates. Results: In multivariate statistical analysis DNA stemline ploidy using 2.2c as a cut‐off value and FIGO stage showed to be statistically significant available presurgery predictors of survival, whereas the postsurgical parameters lymphonodal status, tumor size and parametrial involvement were significantly correlated with survival. The synopsis of all parameters in a multivariate Cox model indicated that – with declining relevance – the number of positive pelvic lymph nodes, DNA stemline ploidy using a cut‐off level at a modal value of 2.2c, largest pelvic lymph node, 5c exceeding rate, and ratio of carcinoma area to cervix area, were of predictive value for survival. Conclusions: Our results suggest that prognostic information deducted from classical staging parameters is successfully complemented by DNA image cytometry which can be applied pretherapeutically.